Acquirement of HRP conjunct IgG anti-IgMs from most widely cultured freshwater fishes in China and its immunoreactivity - ZHOU, XINYI; JIANG, HONGYE; TANG, ZELI; SUN, HENGCHANG; LIN, ZHIPENG; BIAN, QING; YAO, GUANQUN; ZHANG, TIANYOU; CHEN, MEICHENG; ZENG, WEIWEI; YU, XINBING; HUANG, YAN (Academia Brasileira de Ciências, 2021)
Abstract Until now, custom-made or commercial polyclonal antibody against only one kind of fish IgM limited application of the antibody. During our research on development of vaccine against infection of Clonorchis sinensis (C. sinensis) in several kinds of fish, we were conscious of the urgency of secondary antibody to evaluate immune effect and screen C. sinensis infection with immunological technology instead of labor-intensive and time-consuming squash or artificial digestion of fish flesh. So that, we purified IgM of grass carp, bighead carp, crucian carp, common carp and tilapia which were widely cultured freshwater fishes in most areas of China. On this basis, we generated HRP-conjunct rabbit IgG anti-fish IgMs with high titers. IgM of other freshwater fishes including oshima, yellow catfish, bream, silver carp and so on could be recognized by the IgG sensitively. Additionally, The ELISA detection displayed that the IgG could be more specific and sensitive than custom-made rabbit IgG anti-grass carp IgM. The acquirement of HRP-conjunct rabbit IgG anti-fish IgMs was the cornerstone for studying the immune system of teleost fish, developing immunoassay methods and evaluation of fish vaccine with more convenience.